(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
A Banking Sector performs three primary function ineconomy, the operation of the payment system, the mobilization of savings andthe allocation of saving to investment products (Ahluvaliya Montek., S). “Bankas institutions which collects money from those who it to spare or who aresaving it out of their income and lends out to those who required it. [Dr. P. Karthikeyan,2014]”